Subjective Well-being and Burnout on Gender in Lecturers at Private Universities in Lombok Island - Isra Dewi Kuntary Ibrahim; Tifani Dame Hasany; Dhanny Safitri; Siti Riadah (Target : Jurnal Manajemen Bisnis, 2025)
A lecturer is an educator at a university. During their career, lecturers will encounter students with diverse characters. The main duties of a lecturer are teaching, researching, and community service. There are many other administrative duties that a lecturer must carry out. These numerous demands can cause lecturers to experience burnout. Burnout can occur because everyone experiences pressure in their daily activities. Burnout can be reduced by improving an individual’s well-being. Subjective well-being is a state in which individuals perceive and evaluate everything that happens in their lives, namely, cognitive and affective evaluation. Burnout is very likely to affect both men and women. Men are more prone to burnout than women. It is because women experience the same pressures as men, as for men, “working” is an absolute necessity to support their families, whereas for women, this is not the case. Working is not a necessity for women, including in the teaching profession. Therefore, the objective of this study is to analyse whether there is a difference in the effect of subjective well-being on burnout among lecturers at private universities on the island of Lombok, based on gender. The sample consisted of 137 men and 137 women, totaling 174 participants, to represent the phenomenon. The data analysis technique used was Multigroup Analysis (MGA) in PLS-SEM. The study concludes that there is a significant difference between SWB and burnout among male and female lecturers.